CALCULATION OF CONCENTRATION VARIATION [F, OH] THE TOPAZ Al2SiO4 (F1-x, OHx)2 - Flores R., Luis (2007)
With ab-initio calculation carried out the analysis of the electronic properties of the topaz in its fundamental state, with different concentrations of Fluorina (F^(-)) and Hidroxilo (OH^(-)) ions, using the package TB-LMTO-ASA. This compound presents optic properties in its natural form with different concentrations of [F^(-),OH^(-)], as well as to the interaction with ionizing radiation. As a result we will have that as much the total energy as the gap fall in non lineal form to the increase of OH ions, being the topaz with 100% F is but stable that the topaz with OH^(-). Product of this increase takes place a phase transformation, increasing of volume and lowering the energy of Ferrni.